Eight-Section Brocade Exercises Improve the Sleep Quality and Memory Consolidation and Cardiopulmonary Function of Older Adults With Atrial Fibrillation-Associated Stroke - Lv, Wei; Wang, Xinxin; Liu, Jia; Yu, Ping (Frontiers in Psychology, 2019)
Purpose Poor sleep quality is harmful for everyone and potentially even more harmful for the older adults with atrial fibrillation-associated stroke (AFAS). This study aimed to explore the effects of eight-section brocade (ESB) on sleep quality, memory and cardiopulmonary function in the older adults with AFAS. Methods Older adults with AFAS and sleep disorders were recruited and divided into the ESB (EG, n=85) and control groups (CG, general exercise, n = 85). EG patients received 60 min ESB exercises for 5 times a week for 12 weeks; CG patients received normal exercise. Pittsburgh sleep quality index (PSQI) scores (poor sleepers ≥ 8 and normal sleepers < 8), memory for word pairs (poor memory ≤ 7 and normal memory > 7), left ventricular posterior wall (LVPW) thickness, and maximum ventilation (MV, to evaluate cardiopulmonary function) values were measured. The correlation between sleep and memory quality was analyzed by using PSQI scores and word pairs via the test of Pearson correlation coefficients. Adjusted Cox models were used to explore an interaction between PSQI and ESB exercise Results After 12-week exercise intervention, ESB improved sleep quality, latency, duration, disturbance and daytime dysfunction when compared to conventional exercise. In similar cases, the MV values in the EG were also higher than that in the CG (p = 0.009). ESB intervention could not affect cardiac structure and left ventricular ejection fraction. Compared with the CG, the ESB intervention reduced PSQI scores and increased memorized word pairs (p < 0.001 for poor and normal sleepers in both unadjusted and adjusted analysis, p = 0.012 and 0.003 for poor and normal memory). The test of Pearson correlation coefficients showed that PSQI scores were strongly associated with the number of word pairs in both unadjusted and adjusted analyses (p < 0.0001). Conclusions ESB exercise improved sleep quality and memory consolidation and cardiopulmonary function by reducing PSQI scores, increasing word pairs and MV values in the older adults with AFAS.